Regulatory space as factor of change of international investment treaty regime (Journal of actual problems of jurisprudence, 2021)
At present time, the quest of balance between public and private interests under investment treaty provisions has become a serious challenge for all of the concerned parties, namely for host states, foreign investors, arbitral tribunals, scholars and arbitration lawyers. This quest is driving the international investment treaty regime to drastic changes. In this sense, this Article aims to determinate the role of regulatory space factor in the light of changing investment treaty jurisprudence. For this purpose, the Article analyses current fundamental shifts in international investment treaty regime and attempts to explain the roots of these shifts, inter alia, by focusing on the regulatory space factor. It reveals the drawbacks of current treaty regime, the lack of balance between regulatory space and investment protection, the role of the regulatory space in new investment treaties. In conclusion, it would argue that regulatory space plays a pivotal role in overall shifts of treaty regime. It could not resolve the current issues of balance in the treaty regime, but to some extent will serve to strike a balance between the regulatory space and the investment protection. The scientific novelty of the article is determined by the fact that this research attempts to justify the determination of factor of regulatory space in changing investment treaty regime by building a chain of roots of the matter and further development. The subject of the research is international investment law, particularly treaty regime. The Article employs doctrinal methodology to legal research from the perspective of historical, comparative and empirical analysis. The research under this Article is text-based and if applicable supported by the results of empirical studies. Key words: investment treaty regime, regulatory space, investment protection, foreign direct investment, host state, investor, arbitration tribunal, ICSID, BIT, MIT, UNCTAD.